Refugee recognition challenges in India - Shanker, R; Vijayaraghavan, H (Refugee Studies Centre, University of Oxford, 2020)
India has repeatedly signalled its continued commitment to refugee protection and yet its dual system of refugee recognition presents a complex protection picture.